1997
DOI: 10.1177/002215549704500912
|View full text |Cite
|
Sign up to set email alerts
|

Murine Thymic Nurse Cells and Rosettes: Analysis of Adhesion Molecule Expression Using Confocal Microscopy and a Simplified Enrichment Method

Abstract: SUMMARY Thymic nurse cells (TNC) and T-cell stromal rosettes (ROS) are two in vivo models for stromal cell-thymocyte interactions. We describe a simplified enrichment method for TNC and ROS that overcomes the necessity for large amounts of tissue. The complexes were further analyzed with confocal microscopy, and three subunits of ROS were defined on the basis of their central cell phenotype, i.e., macrophage, dendritic, or epithelial cell rosettes. Because adhesion molecules are proposed to play a crucial role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
(6 reference statements)
1
4
0
Order By: Relevance
“…We and others have previously found VCAM-1 expression by thymic stroma (Salomon et al, 1997;Prockop et al, 2002), and we have shown it to be a critical ligand for transcortical migration of intrathymic progenitors (Prockop et al, 2002). Likewise, ICAM-1 has been shown by others to be expressed on various thymocytes, including thymocytes themselves (Reiss and Engelhardt, 1999), nurse cells (Cordes et al, 1997;Oliveira-dos-Santos et al, 1997), and other stromal cells (Reiss and Engelhardt, 1999;Lucas and Germain, 2000). While we did not observe any differences in ICAM-1 expression on vascular cells with respect to the periodicity of progenitor homing, we did observe a difference in the pattern of staining on different types of vessels (see "Results" section), although the implications of this are presently unknown.…”
Section: Discussionsupporting
confidence: 69%
“…We and others have previously found VCAM-1 expression by thymic stroma (Salomon et al, 1997;Prockop et al, 2002), and we have shown it to be a critical ligand for transcortical migration of intrathymic progenitors (Prockop et al, 2002). Likewise, ICAM-1 has been shown by others to be expressed on various thymocytes, including thymocytes themselves (Reiss and Engelhardt, 1999), nurse cells (Cordes et al, 1997;Oliveira-dos-Santos et al, 1997), and other stromal cells (Reiss and Engelhardt, 1999;Lucas and Germain, 2000). While we did not observe any differences in ICAM-1 expression on vascular cells with respect to the periodicity of progenitor homing, we did observe a difference in the pattern of staining on different types of vessels (see "Results" section), although the implications of this are presently unknown.…”
Section: Discussionsupporting
confidence: 69%
“…TNC were isolated as described previously [35]. Collected supernatants were pooled, cells sedimented by a 10 min centrifugation step at 800 × g and resuspended in PBS.…”
Section: Isolation Of Thy-1-expressing Tncmentioning
confidence: 99%
“…This molecule is the main ligant for the CD44 molecule, a transmembrane proteoglycan expressed not only by immature differentiating thymocytes (Lynch and Ceredig, 1989), but also by TEC (Villa-Verde et al, 1994;Patel et al, 1995a;Oliveira-dos-Santos et al, 1997). Moreover, a colocalization of hyaluronic acid and CD44 was evidenced in sections of human thymuses (Patel et al, 1995b).…”
Section: Discussionmentioning
confidence: 96%